Impact of adapted taekwondo vs. multicomponent training on health status in independent older women: a randomized controlled trial - Valdés-Badilla, Pablo; Guzmán-Muñoz, Eduardo; Herrera-Valenzuela, Tomás; Branco, Braulio Henrique Magnani; Hernandez-Martinez, Jordan; Nobari, Hadi (Frontiers in Public Health, 2023)
This study called the TKD & Aging Project, aimed to analyze and compare the effects of an adapted taekwondo program concerning multicomponent training on blood pressure, morphological variables, frequency of food consumption, health-related quality of life (HRQoL), physical fitness, handgrip strength, and postural balance in independent older women. A randomized controlled trial study was conducted with parallel groups for eight weeks (24 sessions of 60 minutes each), double-blind, and repeated measures. Twenty-eight older women initially participated in the intervention. Three participants were excluded due to not performing the re-assessments. Thus, 14 older women were analyzed in the adapted taekwondo group (TKD; age: 62.86 + 2.38 years), and 11 in the multicomponent training group (MCT; age: 63.18 + 1.94 years) participated of final analysis. A two-factor mixed analysis of variance (ANOVA) model with repeated measures was performed to measure the time×group effect. The TKD, showed were significant improvements in mental health (p= 0.024; ES= 0.91) and general health (p< 0.001; ES= 0.75) dimensions of the HRQoL, in the chair stand (p= 0.001; ES= 1.18), arm curl (p< 0.001; ES= 2.10), 2-min step (p< 0.001; ES= 1.73), and chair sit-and-reach (p= 0.001; ES= 0.91) tests, and a significant reduction in postural balance for eyes closed condition in the center of pressure of area (p= 0.021; ES= 0.89), mean velocity (p= 0.004; ES= 0.79), and mediolateral velocity (p< 0.001; ES= 1.26). While, the MCT showed significant increases in the general health (p= 0.013; ES= 0.95) dimension of the HRQoL, and a significantly reduced (p= 0.039; ES= 0.28) the mediolateral velocity of postural balance for the eyes closed condition. The multiple comparisons showed that the TKD achieved significantly higher in chair stand (p= 0.017; ES= 1.79), arm curl (p= 0.003; ES= 1.77), and 2-min step (p= 0.018; ES= 0.91) tests than MCT. Compared to multicomponent training, taekwondo to older women's characteristics improves postural balance and achieves better benefits at the physical fitness and HRQoL level. Therefore, it is possible to recommend it a safe physical activity strategy that showed high adherence to intervention in older women, as long as it is well-dosed.